Education and Roma population - Asensio Belenguer, Ana (Avances en Supervisión Educativa, 2016)
This article deals with Education and the Roma Population. It presents an approach to schooling of Romani children since its outset in the city of Zaragoza (Spain). It analyzes the current status as presented by the Strategy for Social Inclusion of this people 2012-2020, and collects, from various sources, the fact that education remains a pending challenge for Roma Population. Measures to be taken by the educational community from a gender and inclusive perspective are proposed.
Keywords: education; gypsies; students; challenge; educational community; gender; inclusion